REKONSTRUKSI NAMA JEMBER DALAM LAKON BABAD JEMBER LUDRUK SURYA UTAMA - H. Abdillah, Fahmy (UI Scholars Hub, 2024)
This study entitled “Reconstruction name of Jember in Babad Jember Play Ludruk Surya Utama”, is a study of ludruk play that are suspected of having participated in producing or distributing the origins name of Jember, through babad Jember play which performed with Madura, Java and Indonesia language. The reconstruction was based on a structural review; plot, theme, character and toponymy in babad Jember play by Surya Utama group. Examine the mixed use of language based on texture; the dialogue of the Jember babad play which consists of (a) external dialogue in the form of communication between actors, especially in conflicts between characters, (b) internal dialogue in the form of monologues, (c) dialogue that contains elements of humor. The objectives of this study are to find out the pattern name of Jember and the occurrence of language mixing in the ludruk babad Jember play. The study results, the use of Madura, Java, Indonesia languages-which change and mix-that occurs consciously or unconsciously because of the interlocutor factors, message form, situation, topic. Mutual dialogue with different languages is known not to disrupt the storyline. In this case because the actors or performances are held in areas where the people speak Javanese, Madurese and Indonesian. The mixed language that occurs in this case is another form of oral-written Jember chronicle telling using a single language. The overall results can be concluded; (1) name of Jember is given by the character based on the condition of the area and the character's death. (2) Changing and mixing of languages occurs affected by the interlocutors, message form, topic, and situation in which the actor or the performance takes place in the midst of a multilingual society.